Effective Parameter Study for the Facile and Controlled Growth of Silver Molybdate Nano/Micro Rods - Singh, D; Montero-Aravena, M (Higher Education Press, 2016)
Controlled growth of nano/micro structures by controlling the effective parameters is the basic requirement for the application point of view in various areas. Here we report the facile growth of silver molybdate nano/micro rods by mixing the solution of silver nitrate and ammonium molybdate at ambient condition followed by hydrothermal treatment at various temperatures for 12 h. To achieve the goal for the synthesis of long, high yield and homogeneous nanorods various effective parameters have been studied to set the most effective conditions for the growth. Among possible effective parameters first the temperature of the furnace was set by warring the temperature and then at the set temperature the concentration of reactants (NH4)6Mo7O24 and silver nitrate are varied respect to each other. The pH and temperature values were monitored during the mixing of the reactants. Structural/microstructural characterization revealed the optimum condition of 150°C of the furnace and the concentration of (NH4)6Mo7O24 and silver nitrate as described in various tables. © 2016, Higher Education Press and Springer-Verlag Berlin Heidelberg.